A Study on mm-Wave Propagation in and Around Buildings - Leonardo Possenti; Marina Barbiroli; Enrico M. Vitucci; Franco Fuschini; Mattia Fosci; Vittorio Degli-Esposti (IEEE Open Journal of Antennas and Propagation, 2023)
mm-waves are envisaged as a key enabler for 5G and 6G wireless communications, thanks to the wide bandwidth and to the possibility of implementing large-scale antenna arrays and advanced transmission techniques, such as massive MIMO and beamforming, that can take advantage of the multidimensional properties of the wireless channel. In order to analyze in depth the peculiar characteristics of mm-wave propagation, joint measurement and simulation campaigns in indoor and outdoor microcellular environments have been carried out. The investigation highlights that the assumption that mm-wave NLoS connectivity is hardly feasible is not necessarily true as significant reflections, scattering and even transmission mechanisms can provide good NLoS coverage in the considered indoor and outdoor scenarios. This is also reflected in the limited angle-spread differences between LoS and NLoS locations in some cases. Finally, the contribution of different propagation mechanisms (reflection, diffraction, scattering and combination of them) to the received signal is analyzed in the paper with the help of ray tracing simulations. These outcomes can be helpful to predict the performance of mm-wave wireless systems and for the development of deterministic and geometric-stochastic mm-wave channel models.